Studi Psikologis Tentang Dampak Zikir Terhadap Kesejahteraan Mental Di Kalangan Masyarakat Urban - Wulandari Hasibuan, Lumita; Fauziah (Cahaya Ilmu Bangsa Institute, 2024)
Medical professionals reported beginning to understand the relationship between illness and mental health problems as early as the nineteenth century. People with mental illnesses can also suffer from physical disorders, and vice versa, as a result of this reciprocal interaction. Of course, this is closely related to the role of religion in mental health. How do religious teachings affect people's mental health and how does religion affect the way people think? This study will discuss the relationship between religion and mental health and the effects of dhikr therapy. The purpose of this study To find out how religion affects mental health, to find out the effectiveness of dhikr therapy on mental health. Qualitative library research, or library research, is a research methodology. According to research findings, religion plays a role in mental health, including as a life guide, helping to get through difficult times, calming the mind, increasing moral control, mental development, and healing the soul. By getting closer to Allah through dhikr activities to remember Allah, dhikr therapy aims to treat, cure, overcome, and maintain a person's mental health. To get the results of the dhikr, the procedure carried out is to recite the words of dhikr with gratitude.